The importance of integrated marketing communications for the formation of the Country Brand Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
The concepts of methods of forming and using of the brand communication tools has importance not only in large companies and organiza tions, but also in the general structures of country brand. Branding of the country – a strategic decision that requires national zeal and thorough in vestigation, since the state of the brand depends on the general condition of the people, its economy, financial and tourist attraction, the state and the country’s competitiveness. Therefore, in this article are provided espe cially for tools of integrated marketing communications for the formation of the country brand of Kazakhstan. The article includes the history and concept of country brand. Analyzing the importance of creation a country brand, suggested creation a national brand, which consists of the attributes of the Republic of Kazakhstan. There are missions and especially the using of integrated marketing communication. And in particular the using of the schemes listed integrated marketing communication for the formation of the Country Brand Republic of Kazakhstan.
Keywords: brand; branding; the brand of the country; integrated mar keting communications; the country’s image; tourism; export; policies; in vestment; arts; human capital.